Construction and expression of human adiponectin in prokaryotic and eukaryotic expression systems and the study of its effect on selected blood parameters and expression of related genes / Hussin Alwan Rothan Al-Maamuri - Al-Maamuri, Hussin Alwan Rothan (2011)
Adiponectin is one of the most bioactive substances secreted by adipose tissue which is involved in protection against metabolic syndrome, artherosclerosis and type II diabetes. Research into the use of adiponectin as a promising drug for metabolic syndromes requires production of this hormone in high quantities. This may be achieved using recombinant DNA technology, which would also allow the production of different molecular forms as well as providing greater input in terms of understanding its signalling pathway. This study was mainly targeted towards producing adiponectin hormone as a recombinant protein by P. pastoris (P-ADP) as a cheap and convenient eukaryotic expression system for potential application in pharmaceutical therapy. For comparison, adiponectin was also expressed using the E. coli (E-ADP) as a traditional prokaryotic expression system. Following successful expression, the relative bio-properties of P-ADP was assessed in vivo in comparison with E-ADP. Additional studies of the effect of P-ADP on the expression of the genes encoding glucagon, insulin and leptin receptors were carried out. Adiponectin gene was constructed in vitro by splicing its two exons using overlap-extension PCR. Full length adiponectin was amplified by PCR and cloned into pMAL™-p4 vector for expression in E. coli as periplasmic secreted protein. The fusion protein was purified by amylose column after digestion with factor Xa. To express adiponectin in P. pastoris, the full length adiponectin was amplified by cloning into pGEM-T vector and then sub-cloning into pPICZαA vector to be expressed as extracellular secreted protein. The 6xHis-tagged recombinant adiponectin was purified by one step affinity chromatography using Nickel column. SDS-PAGE and western blot were used to detect and analyse the recombinant proteins and Bradford assay was used for protein quantification. Three experiments were designed to assess and compare the effects of E-ADP and P-ADP on blood glucose and lipid profile using ICR mice as a model system. Real-Time PCR was used to examine the changes in the regulation of glucagon, insulin and leptin receptors after administration with P-ADP. The expression of target genes was normalized with β-actin as endogenous gene and the data was statistically analysed based on Δct values and RQ values using t-test. The results showed that adiponectin gene was successfully constructed in vitro by overlap-extension PCR and expressed by E. coli as a soluble periplasm protein and by P. pastoris as a soluble extracellular protein. P. pastoris expression system was successful in producing high molecular weight of adiponectin molecules and relatively high quantity of recombinant protein (0.1 mg/ml) as compared with E.coli (0.04 mg/ml). The optimum conditions of adiponectin production by P. pastoris were 0.5% of methanol induction every 12 hours for 60 hours at 30°C. E-ADP and P-ADP were biologically active in the lowering of blood glucose and triglyceride and increasing high density lipoprotein. The ability of P-ADP in lowering blood glucose was significantly higher than E-ADP. However, there was no significant difference on the effect on lipid profile. P-ADP significantly down-regulates glucagon receptors and up-regulates leptin receptors, whilst there was no significant effect on insulin receptors. Our results suggest that P. pastoris expression system is better in producing high quantity, high biological activity and easily purified recombinant adiponectin comparing with E. coli expression system that can be used in large scale production of adiponectin as potential drugs for metabolic syndromes.